Quantitative evaluation of delamination of graphite by wet media milling - Damm, Cornelia; Nacken, Thomas; Peukert, Wolfgang (Carbon, 2015)
Surfactant-free Few-Layer-Graphene (FLG) suspensions were prepared by wet media delamination of unmodified isostatic graphite in organic solvents using a shaking plate for fast screening of favorable process parameters and a stirred media mill as a delamination tool. The achieved FLG-concentration was determined by a combination of UV/Vis and Raman spectroscopy. A study of wet delamination for different solvents reveals an analogue behavior as for ultrasound-assisted delaminated samples. In N-methylpyrrolidone as dispersing medium the influence of delamination process parameters on FLG concentration was studied and an optimal set of parameters was found. A comparison between various delamination methods shows that delamination by enhanced shear leads to largest flake structures. The highest value for the FLG production rate (produced mass/time) is obtained in a stirred media mill. The formation of FLG was also proved by measuring the flake thickness by atomic force microscopy (AFM). The FLG percentage derived from AFM agrees well with the results determined by statistical Raman spectroscopic analyses.